FUNGSI PENGENDALIAN PENERIMA PROGRAM RUMAH LAYAK HUNI DI KECAMATAN KOTA TIMUR - Yanti Aneta (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
This study aims to find out how the control function of livable housing programs recipients in Kota Timur subdistrict. This researcher uses a qualitative approach. Data collection procedures through observation, interviews and documentation. Data analysis used data reduction analysis, data display and conclusion drawing. The results of the research on the control function of livable housing programs recipients in Kota Timur Subdistrict showed that, 1) Aspects of setting standards and methods are in accordance with the General Criteria set by BAPEMAS, but there are certain policies taken by village and subdistrict officials that are adjusted to the conditions in the field, which is usually called a special condition; 2) The aspect of performance measurement shows that the village officials, subdistrict officials have carried out performance measurements based on the rules that have been set; 3) Aspects of Retrieval Corrective Action shows that the parties concerned have coordinated in order to carry out improvements both in the process of planning the determination of livable housing programs recipients and the process of implementing a livable housing program. Research suggestions are related parties consisting of a village, subdistrict, and housing officials and the Gorontalo city settlement area to further intensify coordination and intensive evaluation in terms of determining the recipient community of livable housing programs to be accepted by those who really have the right to receive this program